Load and frequency dependent CMOS dual-mode DC-DC converter. (October 2019) - Lee, Chan-Soo; Kim, Sung-Soo; Yu, Jun-Ho
Abstract: In this paper, CMOS integrated dual-mode DC-DC buck converter is proposed for portable application. The proposed dual-mode converter is designed to be controlled by PFM (pulse frequency modulation) or PWM (pulse width modulation) modes which depend on the range of the output current. The PWM/PFM dual-mode converter, which is used for the application of wide current range and high power efficiency, is to generate the output voltage of 0.5–3.0 V with the battery source of 3.3–5.0 V and the load current in the range of 5–250 mA. In the load-current under 80 mA, PFM control is applied to obtain high power efficiency, while PWM is designed to be operated in a higher range of the load-current. A ring-type VCO (voltage-controlled oscillator) is used in PFM circuit and provides a variable frequency to correspond to the output current. In PWM control circuit, the combination of sensing current and ramp signal is applied in feedback circuit of converter. The proposed dual-mode DC-DC buck converter is integrated with 0.35 μm CMOS process. Simulation result shows that the converter provides the well-regulated line and load regulations with power efficiency of 78–82% in the load range of 10–250 mA.